Telkupi, a submerged temple site in West Bengal - Mitra, Debala; Archaeological Survey of India ([New Delhi] : Archaeological Survey of India, 1969)
Articles with reference to Telkupi, village located in Purulia District of West Bengal, India.
Keywords: Hindu temples -- India -- Telkupi; Telkupi (India) -- Antiquities